Chemical Scarification and Ozone in Seed Dormancy Alleviation of Wild and Domesticated Opuntia, Cactaceae. (4th March 2017) - Monroy Vázquez, María Elena; Peña-Valdivia, Cecilia Beatriz; García, José Rodolfo; Solano, Eloy; Campos, Huitziméngari; García, Eduardo
ABSTRACT: Protocols for seed germination in the Opuntia genus are different and unsuitable for all their species. Dormancy of Opuntia seeds can be modified by the combination of scarification and an oxidizing agent such as O3, which could induce antioxidant and DNA-repair mechanisms or dormancy-breaking effects in hydrated seeds. The objective of this study was to evaluate the effects that the combination of mechanical and chemical scarification with exposition to sub-lethal O3 doses have on seed germination and seedling growth of O. streptacantha Lem., O. megacantha Salm-Dyck, and O. ficus-indica (L.) Mill. Our hypothesis was that O3 favors germination on scarified seeds and that the magnitude of the effect is species-dependent. Water uptake and germination were quantified in seeds every 48 h, until their roots reached a 5-mm length. The results were analyzed with an analysis of variance and multiple means comparisons with the Tukey test. Accelerated water uptake was observed during the first 48 h; the maximum average was 33.5% in all species. The combination of acid scarification and imbibition in the presence of O3 increased ( P  ≤ 0. 05) germination (between 17.8 and 44.4%), mainly in O. streptacantha . O3 increased germination, regardless of the species. O3 can be used in sublethal doses to increase seed germination and seedling development in Opuntia genus.